Parallel radon and thoron measurements in mineral sand mining area of Ha Tinh province - Bui , Dac Dung; Trinh , Van Giap; Tibor , Kovacs; Tran , Ngoc Toan; Le , Dinh Cuong; Tran , Khanh Minh; Nguyen , Huu Quyet; Nguyen , Van Khanh (Nuclear Science and Technology, 2013)
In this study, we have tested the possibility of parallel measurement of radon (222Rn) and thoron (220Rn or Tn) by alpha track detectors at the extraction and processing of black sands that contains high content of Zircon and Monazite minerals in a coastal area of the Ha Tinh province. A pair of cylindrical cups RADUET, designed to separately measure Rn and Tn with CR-39 detectors (Radosys Company Ltd – Hungary), were used for the test. The results showed that concentrations of indoor Rn and Tn in the black sand extraction area are not high (28 ± 6 Bq/m3 for Rn, 14 ± 5 Bq/m3 for Tn). The Rn and Tn concentrations in the indoor air of the titanium processing plant are 34 ± 6 Bq/m3 for Rn, 58 ± 11 Bq/m3 for Tn, and are higher than those concentrations in the residential houses outside the plant (20 ± 4 Bq/m3 for Rn, 16 ± 8 Bq/m3 for Tn) but still comparable to the average concentrations of indoor Rn and Tn reported by the UNSCEAR 2006. At Zircon processing plant, indoor Rn concentrations are similar to those in the titanium processing plant but Tn concentrations in the houses for separating Rutile and Zircon are very high. Indoor Tn concentration is especially high in the house for separating Zircon where it could reach 2931 Bq/m3, hundred times higher than that in the surrounding residential houses and that of the world average published by UNSCEAR 2006.